2019
DOI: 10.1186/s12882-019-1210-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in patients with myocardial infarction undergoing percutaneous coronary intervention using radial versus femoral access

Abstract: BackgroundData on radial access (RA) as an independent risk factor for acute kidney injury (AKI) in myocardial infarction (MI) patients are conflicting. Our aim was to assess how RA influences the incidence of AKI in MI patients undergoing percutaneous coronary intervention (PCI).MethodsData from 3842 MI patients undergoing PCI at our institution from January 2011 to December 2016, of which 35.8% were performed radially, were retrospectively analyzed. A propensity-matched analysis was performed to adjust for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…A total of 5 studies were then excluded, as 2 reported data (16,17) from an already included RCT and the other 3 studies (18-20) did not report on the incidence of AKI. A total of 14 studies were included in this systematic review and meta-analysis (8)(9)(10)(11)(12)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 5 studies were then excluded, as 2 reported data (16,17) from an already included RCT and the other 3 studies (18-20) did not report on the incidence of AKI. A total of 14 studies were included in this systematic review and meta-analysis (8)(9)(10)(11)(12)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies ( 8 , 10 ) were RCTs, while the remaining studies were retrospective in nature. Furthermore, six retrospective studies utilized propensity score matching to harmonize the baseline characteristics of the study participants ( 9 , 12 , 22 , 25 , 27 , 29 ). In the included studies, participants underwent coronary catheterization for a variety of reasons.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations